Bone regeneration in the posterior maxillary region for installation of dental implants - Rudys Rodolfo De Jesus Tavarez; Adriana Santos Malheiros (Editorial Ciencias Médicas, 2017)
Introduction: bone regeneration of the posterior maxilla is an important feature to enable correct placement of implants and thus allow an adequate prosthetic rehabilitation. Several surgical techniques are reported, since the form of access to the sinus, elevation of Schneider membrane and fill the cavity. Objective: to address the resources used in bone regeneration surgery of the posterior maxilla and the effectiveness of the methods applied. Methods: an electronic search of the literature was performed in the databases LILACS, MEDLINE and BBO studies published in English and Portuguese. The inclusion criteria were considered articles between 2000 and 2014, with the key words that guided the search were: maxillary bone regeneration, Schneiderian membrane, maxillary sinus lift. 1 529 articles were obtained, of which 27 selected articles relevant to the study. Exclusion criteria were eliminated in the articles which were in the year below 2008 and fleeing the matter at hand. Data analysis and integration: it was found that the traditional technique of access to the maxillary sinus with the use of drills, lifting the membrane through curettes, and the regeneration itself with autogenous bone graft and/or heterogeneous continue as the most commonly used, however alternative as less invasive ultrasonic technology to access, hydrodissection to raise the Schneider membrane and biomaterials to fill the cavity emerge as viable, with favorable results options. Conclusions: there is a direction in the search for methods and materials that reduce the morbidity of traditional techniques and which offer satisfactory results in the short and long term. The use of surgical techniques less invasive and use of biomaterials are among the advances for the regeneration of the posterior maxilla.